Effectiveness of Free and Liposome-Entrapped Antitumoral Drugs against Hepatocellular Carcinoma: A Comparative In vitro Study - Gomes, André da Silva (2023)
Oncohematology department. Oncobio Hospital. Belo Horizonte, MG, Brazil / Medical BSc Program. University Vale do Rio Doce. Governador Valadares, MG, Brazil.